Utilization and outcomes of cervical cancer screening services in Harare City, 2012-2016: a secondary data analysis - Christine Gabaza; Prosper Chonzi; Addmore Chadambuka; Gerald Shambira; Tsitsi Patience Juru; Notion Tafara Gombe; Peter Nsubuga; Mufuta Tshimanga (BMC, 2019)
Abstract Background Visual inspection with acetic acid and cervicography (VIAC) is a method used to screen for cervical cancer. VIAC can be used as part of a "see and treat" strategy. Nine Harare city council health facilities offer VIAC free of charge with the aim of reducing morbidity and mortality from cervical cancer. Between 2014 and 2016, the number of women utilising VIAC dropped by 35%. We analysed records of clients who utilise VIAC at Harare city health facilities to characterise women accessing VIAC and their outcomes to make recommendations for improving the services. Methods We conducted a descriptive cross-sectional study using data collected for the Harare city VIAC program. We analysed all records of clients who utilised VIAC services at nine Harare city health facilities from 1 May 2012 to 31 December 2016. Results We analysed 46,217 records, the median age of the clients was 34 years [Q1 = 27: Q3 = 42]. Of the 46,217 clients screened, 3001 (6.5%) were VIAC positive, and 512 (1.1%) had suspicious of cancer lesions. The prevalence of VIAC positive ranged from 58 to 74 per 1000-screened clients over the 5 years. The prevalence of suspected cancer ranged from 9 to 14 per 1000-screened clients, and there was a general decrease in the prevalence between 2012 and 2016. Of the 3513 clients with VIAC positive or had suspicious of cancer lesions, 2090 (74.1%) did not receive treatment at the site where the screening took place. Conclusion The majority of women who are accessing VIAC services in Harare are middle-aged, multiparous and married women. There is a treatment gap at most of the VIAC centres such that clients are referred to other centres for management. The objective of "see and treat" is not being realised.